Analisis Implementasi Sistem Informasi Strategik Untuk Pencapaian Sasaran Strategi (Studi Kasus BPK-RI Perwakilan Banjarmasin) - , Suyono ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Badan Pemeriksa Keuangan (BPK) as an institution examiner is relying on information management, including the representative office in Banjarmasin. Therefore, the Information Technology Systems is expected to be a weapon or placed as an organizational strategy of Strategic Information Systems. This study aimed to explain how situational factors and organizational processes provide impetus (facilitator) and barriers (inhibitors) in the application of SIS in Banjarmasin Representative Office and explains how the role of current information technology systems. In order to achieve these research goals, problems analyzed using analysis factors of SIS Implementation. This analysis was developed by William R. King (1996) which makes the formulation of the key factors that influence the organization in implementing the SIS.These factors can be categorized in two roles, factors that facilitate the implementation of SIS and the factors that hinder the implementation of SIS. The factors that facilitate the implementation of SIS are : business needs, the needs of innovation, competitive positioning, environment, economies of scale, and the direction of top management. While the factors that hinder the implementation of SIS are: triggers of IT, the need for innovation, and economies of scale. Based on the results of research conducted, it is known that the factors that should be facilitator has not been able to encourage organizations to implement the SIS. Only high business needs and the needs of high economies of scale that tend to encourage the organization. Innovation needs and direction of top management and competitive position has not provided a positive impetus.